Computer Networks Use of Vlan (Virtual Local Area Network) Technology in Modelling and Grouping - Nasiba Ashurovna Kayumova; Shokhista Yusup's Fayziyeva Qizi (Genius Journals, 2023)
Kayumova N.A., Fayziyeva Sh.F.Kompyuter tarmoqlari modellariniyaratuvchi dasturlardan foydalanish.https://cajecs.com/index.php/cajecs/article/ view/26/v1i282. Каюмова Н. А., Суропов Б. М.ПСИХОЛОГО-ПЕДАГОГИЧЕСКИЕАСПЕКТЫ В ПРОЦЕССЕ ОБУЧЕНИЯИНФОРМАЦИОННОКОММУНИКАЦИОННЫ ТЕХНОЛОГИИ//Интернаука. –2019. – №. 28. – С. 66-67.3. NA Kayumova, BM Suropov.Improvement of the methodologicalsystem for training computer tea chersbased on the integration approach.https://www.cibgp.com/article_9883.html4. КАЮМОВА Н. А. THE NEWTECHNOLOGIES IN THE ORGANIZATIONOF THE ELECTRONIC LEARNINGENVIRONMENT IN HIGHER EDUCATION//Современноеобразование(Узбекистан). –2021. – №.2. – С. 64-73.5. Каюмова Н. А. ОЛИЙ ТАЪЛИМДАЭЛЕКТРОН ТАЪЛИМ МУҲИТИНИТАШКИЛ ЭТИШДА ЯНГИТЕХНОЛОГИЯЛАР //Современноеобразование (Узбекистан). –2021. –№. 2 (99). – С. 64-73.
Keywords: Cisco Packet Tracer; VLAN; switch